The effects of game therapy on the static and dynamic balance of 4-10-year-old children with spastic diplegic cerebral palsy - Maryam Emami Korande; Amirhossein Barati; Mina Haghighi; Pejman Javid (Sport Sciences and Health Research)
Background: Balance is a critical physical factor for achieving independence, and children with spastic cerebral palsy often experience motor and balance difficulties.Aim: The aim of this study was to investigate the effects of game therapy on the balance of children with cerebral palsy, with a focus on basic abilities.Materials and Methods: This study utilized a quasi-experimental design with a pretest-posttest controlled approach. Twenty children aged 4-10 years, diagnosed with spastic diplegic cerebral palsy with levels 1 and 2 according to SCFMG standards, with a minimum IQ of 80 (to be able to perform the required tasks), and possessing the basic ability to stand and maintain posture balance, as well as communicate and understand linguistic concepts, were randomly selected from rehabilitation clinics in Tehran. Subjects were randomly divided into the control and game therapy groups. The pediatric balance scale (PBS) test was used to evaluate the balance level using a WII device with a wireless controller and a motion controller. The exercise program consisted of nine different games targeting various areas with the common goal of improving the child's balance. After 20 game therapy sessions, (four 20-minute sessions per week,) tests were repeated in the post-test. The data were analyzed with tow way ANOVA Test and paired T-test by SPSS, 20.Results: The results of the paired t-test indicate a significant improvement in static balance in the post-test for the game therapy group when compared to the pre-test (P<0.0001). Moreover, the dynamic balance of the experimental group showed a significant improvement in the post-test when compared to the pre-test (P=0.042).Conclusion: The study findings indicate that game therapy is a viable method for enhancing both static and dynamic balance in children with cerebral palsy. Given that the games used in the therapy are intended to be played at home with parental supervision, it is advised that these games be utilized to improve the balance of children with cerebral palsy.